Individual physiological and mitochondrial responses during 12 weeks of intensified exercise. Issue 15 (29th July 2021) - Jacques, Macsue; Landen, Shanie; Alvarez Romero, Javier; Yan, Xu; Garnham, Andrew; Hiam, Danielle; Siegwald, Mélina; Mercier, Emma; Hecksteden, Anne; Eynon, Nir; Voisin, Sarah
Abstract: Aim: Observed effects of exercise are highly variable between individuals, and subject‐by‐training interaction (i.e., individual response variability) is often not estimated. Here, we measured mitochondrial (citrate synthetase, cytochrome‐c oxidase, succinate dehydrogenase, and mitochondrial copy‐number), performance markers ( W peak, lactate threshold [LT], and V O2peak ), and fiber type proportions/expression (type I, type IIa, and type IIx) in multiple time points during 12‐week of high‐intensity interval training (HIIT) to investigate effects of exercise at the individual level. Methods: Sixteen young (age: 33.1 ± 9.0 years), healthy men ( V O2peak 35–60 ml/min/kg and BMI: 26.4 ± 4.2) from the Gene SMART study completed 12‐week of progressive HIIT. Performance markers and muscle biopsies were collected every 4 weeks. We used mixed‐models and bivariate growth models to quantify individual response and to estimate correlations between variables. Results: All performance markers exhibited significant ( W peak 0.56 ± 0.33 p  = 0.003, LT 0.37 ± 0.35 p  = 0.007, V O2peak 3.81 ± 6.13 p  = 0.02) increases overtime, with subject‐by‐training interaction being present (95% CI: W peak 0.09–0.24, LT 0.06–0.18, V O2peak 0.27–2.32). All other measurements did not exhibit significant changes. Fiber type IIa proportions at baseline was significantly associated with all physiological variables ( p  < 0.05), and citrate synthetase and cytochrome‐c oxidase levels at baseline and overtime (i.e., intercept and slope) presented significant covariance ( p  < 0.05). Finally, low correlations between performance and mitochondrial markers were observed. Conclusion: We identified a significant subject‐by‐training interaction for the performance markers. While for all other measures within‐subject variability was too large and interindividual differences in training efficacy could not be verified. Changes in measurements in response to exercise were not correlated, and such disconnection should be further investigated by future studies. Abstract : Exercise training leads to whole body and tissue‐specific adaptations. However, the observed effects of exercise are highly variable between individuals, and subject‐by‐training interaction (i.e., individual response variability) is often not estimated. Here, we measured mitochondrial (citrate synthetase, cytochrome‐c oxidase, succinate dehydrogenase and mitochondrial copy‐number), performance markers ( W peak, lactate threshold, and V O2peak ) and fiber type proportions/expression (type I, type IIa, and type IIx) in multiple time points during 12‐week of high‐intensity interval training to investigate effects of exercise at the individual level, and if measurement changes in different domains covary each other as exercise goes by.